INTERNALISASI KARAKTER RELIGIUS DAN SOSIAL SISWA MTS MIFTAHUL ULUM DAN PPKP RIBATHUL KHAIL - Muhammad Junaidi; Muh. Abzar Duraesa; Badrut Tamam (STKIP Pesisir Selatan, 2026)
Internalization of Religious and Social Character among Islamic Junior High School Students: A Multisite Study at MTs Miftahul Ulum Sebulu and PPKP Ribathul Khail Tenggarong. Master's Thesis, Islamic Education Study Program, Graduate School of UIN Sultan Aji Muhammad Idris Samarinda. This study employed a qualitative phenomenological approach with a multisite research design aimed at analyzing the process of internalizing religious and social character, the supporting and inhibiting factors, and the implications for students’ character development. Data were collected through participant observation, in-depth interviews, and document analysis, and were subsequently analyzed using data reduction, data display, and conclusion drawing procedures. The findings revealed that the internalization of religious and social character was implemented through the integration of character values into classroom instruction, religious habituation activities such as congregational prayers and Qur’anic recitation, teachers’ role modeling in daily life, and social activities including mutual cooperation and collaborative work among students. The primary supporting factors included a religious school culture, parental support, and the commitment of all school stakeholders. Meanwhile, inhibiting factors consisted of the negative influence of social media, limited supervision outside the school environment, and differences in students’ family backgrounds.